Leadership Lessons from Westeros: A Qualitative Case Study on Game of Thrones as a Springboard for School Leadership Learning among Filipino Gen Z In-Service Teachers - Obmerga, Marwin (GILE Journal of Skills Development, 2026)
As Generation (Gen) Z enters the teaching profession, understanding the foundational skills (propaedeutics) required for future effective school leadership is critical. Considering their emergent organisational behaviour patterns, Game of Thrones (GOT) offers rich narratives and tropes that illustrate strategic planning, navigating tensions, and cultivating relational influence, providing a compelling lens for informal leadership learning. This qualitative case study explored twelve (12) purposively selected Filipino Gen Z in-service teachers, examining how engagement with GOT television series informs their preliminary preparation for school leadership. Semi-structured interviews captured participants’ reflections, which were analysed through Thematic Analysis. The study advances a nuanced Typology of GOT Popular Culture-driven Propaedeutics for School Leadership Learning among Filipino Gen Z in-service teachers, foregrounding three (3) interrelated themes: the Logistics of School Leadership, the Politics of School Leadership, and the Rhetorics of School Leadership. These themes captured how participants made sense of operational decision-making, power negotiations, alliances, moral tensions, and persuasive communication through familiar GOT episodes, and how such sensemaking functioned as an accessible springboard for reflecting on school leadership aspects. Theoretically, the findings enrich modern leadership learning and preparation by illustrating how popular culture mediated contexts can cultivate early leadership cognition, ethical discernment, and strategic awareness among emerging educational leaders. Practically, the study demonstrates how thoughtfully curated popular culture elements may be harnessed within formal and informal professional learning spaces to align with Gen Z teachers’ interpretive routines, thereby strengthening their readiness for future leadership and influence within contemporary educational organisations.